2016
DOI: 10.18549/pharmpract.2016.02.699
|View full text |Cite
|
Sign up to set email alerts
|

Improving pediatric liquid medication labeling of the hospital information system in Malaysia: qualitative analysis of pharmacists’ perceptions

Abstract: Background:Inadequacies of drug labeling have been frequently reported among Malaysian healthcare institutes, in which the Hospital Information System (HIS) is used.Objective:To identify potential areas to improve the existing labels used for pediatric liquid medications.Methods:This study was qualitative in nature, whereby focus group discussions (FGDs), face-to-face interviews (FTFIs), and onsite observation were used for data collection. Pharmacists stationed at three units (outpatient, inpatient and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Similarly, a study from Malaysia proved the positive role of pictograms in improving the quality of use of oral liquid medicines. Another study suggests that pictograms significantly increased dosing accuracy [ 25 ]. The results of a recently published analysis of 771 studies aiming to improve therapeutic adherence showed that healthcare professionals should focus more on behavioral interventions, especially those based on the development of drug use habits, than on cognitive strategies to change the knowledge and beliefs of patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study from Malaysia proved the positive role of pictograms in improving the quality of use of oral liquid medicines. Another study suggests that pictograms significantly increased dosing accuracy [ 25 ]. The results of a recently published analysis of 771 studies aiming to improve therapeutic adherence showed that healthcare professionals should focus more on behavioral interventions, especially those based on the development of drug use habits, than on cognitive strategies to change the knowledge and beliefs of patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 3 4 14 ] Usually adherence to treatment is poorer in chronic diseases such as psoriasis due to various factors including difficulty in applying the topical medication, social factors, and treatment-related factors such as satisfaction with the treatment and complexity of the treatment protocols. [ 2 3 4 9 , 15 ] The use of easy-to-understand labels may help patients to understand the medications more easily, and hence may reduce the counseling time spent by pharmacists during dispensing. Furthermore, in a multiethnic population such as us, language and comprehensibility is one of the restricting factors for health-care providers to deliver the information.…”
Section: R Esults and Discussionmentioning
confidence: 99%
“…Furthermore, in a multiethnic population such as us, language and comprehensibility is one of the restricting factors for health-care providers to deliver the information. [ 15 ] Therefore, labeling aids such as color and picture are helpful to assist the tasks of health-care personnel and patient comprehension.…”
Section: R Esults and Discussionmentioning
confidence: 99%
“…The control group received their liquid medications along with a text‐only label generated by the e‐Hospital Information System (e‐His), which has the dose expressed in millilitres (ml) . Instead, a new label, which incorporated an image of measuring scale of a 10‐ml syringe to illustrate volume to measure, was provided to the intervention group (Figure ).…”
Section: Methodsmentioning
confidence: 99%